Rational quadratic Bézier curve fitting by simulated annealing technique - Najihah, Mohamed; Ahmad, Abd Majid; Abd Rahni, Mt Piah (AIP Publishing LLC, 2013)
A metaheuristic algorithm, which is an approximation method called simulated annealing is implemented in order to have the best rational quadratic Bézier curve from a given data points. This technique is used to minimize sum squared errors in order to improve the middle control point position and the value of weight. As a result, best fitted rational quadratic Bézier curve and its mathematical function that represents all the given data points is obtained. Numerical and graphical examples are also presented to demonstrate the effectiveness and robustness of the proposed method.